Petrological and chronological study of primitive high-Mg andesite from monogenetic volcanoes in the fore-arc region of northern Kamchatka Peninsula - Nishizawa Tatsuji; Nakamura Hitomi; Churikova Tatiana; Gordeychik Boris; Ishizuka Osamu; Iwamori Hikaru (Hokkaido University, 2014)
Primitive high-Mg andesites (HMA) exhibit low FeO*/MgO (FeO*, total iron) and high Mg# (=100×Mg/(Mg+Fe)), and are thought to be generated by hydrous mantle melting (Kushiro, 1969). HMA, including sanukitoids of the Setouchi volcanic belt, have been recognized in many orogenic belts of various ages, and in several cases, constitute a part of ophiolite (Tatsumi, 2003). Therefore, occurrence of HMA in northern Kamchatka may have important implications on the tectonic setting of the peninsula and/or the melting condition underneath.